VSR symmetries in the DKP algebra: The interplay between Dirac and Elko spinor fields - Cavalcanti, R. T.; Hoff da Silva, J. M. [UNESP]; Rocha, Roldao da (Springer, 2014)
VSR symmetries are here naturally incorporated in the DKP algebra on the spin-0 and the spin-1 DKP sectors. We show that the Elko (dark) spinor fields structure plays an essential role in accomplishing this aim, unravelling hidden symmetries on the bosonic DKP fields under the action of discrete symmetries.